2013
DOI: 10.1186/1471-2164-14-833
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptomic approach to elucidate the physiological significance of human cytochrome P450 2S1 in bronchial epithelial cells

Abstract: Background: Cytochrome P450 2S1 (CYP2S1) is an orphan P450 with an unknown biological function. Data from our laboratory and others suggest that CYP2S1 may have an important physiological role in modulating the synthesis and metabolism of bioactive lipids including prostaglandins and retinoids. CYP2S1 expression is elevated in multiple epithelial-derived cancers as well as in the chronic hyperproliferative disease psoriasis. Whether CYP2S1 expression in proliferative disease is protective, detrimental, or neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Indeed, CYP2S1 affected the metabolism of arachidonic acid (AA) and linoleic acid (LA) to modulate BEAS-2B cells growth. [17] In consistent with their results, our data also found CYP2S1 was enriched in Lipid metabolic process. It will be interesting to investigate the detailed mechanism by which CYP2S1 regulate lipid metabolism in PC in future study.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, CYP2S1 affected the metabolism of arachidonic acid (AA) and linoleic acid (LA) to modulate BEAS-2B cells growth. [17] In consistent with their results, our data also found CYP2S1 was enriched in Lipid metabolic process. It will be interesting to investigate the detailed mechanism by which CYP2S1 regulate lipid metabolism in PC in future study.…”
Section: Discussionsupporting
confidence: 92%
“…Study showed that expressions of 8 CYPs were changed in CYP2S1-depleted cells, and all of them were involved in lipid biotransformation. Indeed, CYP2S1 affected the metabolism of arachidonic acid (AA) and linoleic acid (LA) to modulate BEAS-2B cell growth [ 18 ]. In consistent with their results, our data also found CYP2S1 was enriched in lipid metabolic process.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2S1 mRNA expression level is low in liver, but high in extrahepatic tissues such as respiratory and digestive systems. 10 In addition, CYP2S1 mRNA and protein are also expressed in human skin. CYP2S1 plays an important physiological role in the metabolism of dodecanoids, and may play a role in inflammatory response, tumor, and other pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…13.2, including 9 exons, encoding 504 amino acid proteins with molecular weight of about 55.8 kDa, with 8 single‐nucleotide polymorphisms (SNPs) loci. CYP2S1 mRNA expression level is low in liver, but high in extrahepatic tissues such as respiratory and digestive systems 10 . In addition, CYP2S1 mRNA and protein are also expressed in human skin.…”
Section: Discussionmentioning
confidence: 99%